Collaborative Application of CTL Learning Model with Conventional Model on Student Learning Outcomes in Geography Lessons - Rahmayoni Rahmayoni; Yurni Suasti; Ernawati Ernawati (International Journal of Educational Dynamics, 2021)
There are still many students who are less motivated to do the assignments given during the theoretical and practical material, both those given in class and as homework assignments. The solution for solving this problem by using collaborative methods of contextual learning teaching (CTL) and problem-based learning (PBL) in geography subjects can improve student learning outcomes. This study aims to apply the contextual learning teaching (CTL) model with the conventional model to student learning outcomes in geography. This research method uses experimental research. The population in this study is the total sample of XI Social Science 3 students. Data was collected using a pre-test and a post-test. The results of this study have a positive difference and a significant influence between the CTL learning method and the conventional method on student learning outcomes.